1986
DOI: 10.1093/nar/14.5.2157
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genome structure of tobacco rattle virus strain PSG

Abstract: The sequence of the 3'-terminal 2077 nucleotides of genomic RNA 1 and the complete sequence of genomic RNA 2 of tobacco rattle virus (TRV, strain PSG) has been deduced. RNA 2 (1905 nucleotides) contains a single open reading frame for the viral coat protein (209 amino acids), flanked by 5'- and 3'-noncoding regions of 570 and 708 nucleotides, respectively. A subgenomic RNA (RNA 4) was found to lack the 5'-terminal 474 nucleotides of RNA 2 and is the putative messenger for coat protein. The deduced RNA 1 sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…Taken together, the two kinds of experiment show that the bulk of the sequences in RNA-1 and RNA-2 are generally dissimilar, but that the 3' ends are an exception. Similar sequences at the 3' ends of each of the genome parts have been found for several other plant viruses with divided genomes, including alfalfa mosaic virus (Koper-Zwarthoff et aL, 1979), brome mosaic virus (Dasgupta & Kaesberg, 1977), CPMV (Davies et al, 1979), cucumber mosaic virus (Symons, 1979) and tobacco rattle virus (Bergh et al, 1985;Cornelissen et al, 1986). It seems likely that these similarities are of functional significance, probably as recognition signals for one or more proteins involved in the viruses' life cycles.…”
Section: Discussionmentioning
confidence: 58%
“…Taken together, the two kinds of experiment show that the bulk of the sequences in RNA-1 and RNA-2 are generally dissimilar, but that the 3' ends are an exception. Similar sequences at the 3' ends of each of the genome parts have been found for several other plant viruses with divided genomes, including alfalfa mosaic virus (Koper-Zwarthoff et aL, 1979), brome mosaic virus (Dasgupta & Kaesberg, 1977), CPMV (Davies et al, 1979), cucumber mosaic virus (Symons, 1979) and tobacco rattle virus (Bergh et al, 1985;Cornelissen et al, 1986). It seems likely that these similarities are of functional significance, probably as recognition signals for one or more proteins involved in the viruses' life cycles.…”
Section: Discussionmentioning
confidence: 58%
“…For example, there is a match of 12 nucleotides in maize chlorotic mottle virus R N A (Lommel et al, 1991), up to 10 in tobacco rattle virus R N A (TRV; Cornelissen et al, 1986) and up to 11 in alfalfa mosaic virus R N A (Symons, 1985). As suggested by Cornelissen et al (1986) for T R V R N A , this sequence similarity at the 5' ends may reflect a replicase recognition signal in the corresponding minus-strand RNA.…”
Section: Discussionmentioning
confidence: 99%
“…The partial sequence obtained for the anomalous TRV isolate N5 RNA-2 is not inconsistent with it having a similar origin. We suggest that the existence of such a common region at the 5' termini of tobravirus RNA-2 molecules, combined with spurious subgenomic promoter-like elements at the 3' termini of RNA-I molecules (Angenent et al, 1986;Cornelissen et al, 1986), may provide the tobraviruses with the previously suggested means to accommodate RNA-2 molecules with different termini. These sequences could enable their replication by enzymes encoded by the different RNA-1 molecules of the three tobraviruses (Angenent et al, 1986).…”
mentioning
confidence: 88%